CARE PROJECT CARING (Fiep Bulletin - online, 2019)
Introduction: Natural components of the identity constitution; stress, anxiety, depression and poor self-esteem canaffect the overall health of the subject. When adaptation and recovery are not feasible, the process of illness is installed,demanding professional intervention. Labor contingencies can serve as predisposing factors, and the theoretical and practicalproduction of prevention and health promotion responses to the affected population is paramount. For this, it is imperative thehumanized multidisciplinary work that contemplates the integral health of the individual, contributing to their quality of life andwell-being. Objective: to verify the level of stress, anxiety, depression and self-esteem, after applying the Quick Massage inergonomic chair. Methodology: Comparative and qualitative, with intervention in two stages with the educational body of theBrás-Móoca CEI in the city of São Paulo, through the application and analysis of scales of stress, anxiety, depression and selfesteem,with subsequent therapeutic intervention from massages, dynamics, conversation wheels and distribution of informativeleaflets and cosmetic kits for 22 (twenty-two) educators of the institution. Results: 31.8% of the teachers presented signs ofstress, 68.17% of anxiety, 59.07% of depression and 13.63% of self-esteem decreased. Thus, of the 22 participants, about 7showed signs of stress, 15 of anxiety, 12 of depression and 3 of impaired self-esteem. The present results are representative ofthe mind-body suffering circumscribed in the work environment, and more specifically, contemporary educational. FinalThoughts: After the massages the spontaneous responses were lightness, feeling of well being, more disposition, less stressed,less anxious and more lively. The performance made possible the learning through work, the establishment of professionalpatientbond and the response to the demands of the target public through listening, receiving, orientation and therapy. At thelimit, the relevance of integrated and interdisciplinary work remains to build a unified, contextual and effective health systemamong its users.